PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN MAHASISWA MEMILIH STMIK BINA MULIA PALU - Podungge, Emil Salim (Katalogis, 2015)
The research aims to explore and analyze the influence of service marketing mix that includes: product, price, promotion, place, people, process, physical evidence and productivity and quality, on students’ decisions to select STMIK Bina Mulia, Palu. The study is descriptive quantitative and it consists of 73 students who were selected as respondents thorough Probability Proportional to Size sampling method. Based on analysis using Multiple Linear Regressions, it is found that service mix that consist of product, price, promotion, place, people, process, physical evidence and productivity and quality, has significant influence on students’ descision to select STMIK Bina Mulia Palu. Partially, promotion (X3) has insignificant influence on students’ decision to select STMIK Bina Mulia Palu.